Massive haemoptysis in an intravenous drug user with infective tricuspid valve endocarditis. (24th August 2010) - Müller, Karin Anne Lydia; Zürn, Christine Stefanie; Patrik, Htun; Heuschmid, Martin; Hetzel, Jürgen; Henning, Andreas; Müller, Iris Irmgard; Lamprecht, Georg; von Weyhern, Claus; Herdeg, Christian; Ziemer, Gerhard; Gawaz, Meinrad Paul; et al.
Abstract : Major causes of morbidity in intravenous drug users are infections. In infective endocarditis, the tricuspid valve is mainly involved. Masses can cause septic embolisms and, in rare cases, they are associated with mycotic aneurysms of pulmonary arteries that lead to severe haemorrhage. We report the case of a young woman with a history of intravenous drug abuse and prolonged infective tricuspid valve endocarditis. Initially, echocardiography showed large masses on the anterior leaflet of the tricuspid valve and severe tricuspid regurgitation; blood cultures revealed staphylococcus and streptococcus species. Eight months after initial diagnosis, she presented with severe haemoptysis and fever. CT revealed a ruptured mycotic aneurysm of the right pulmonary artery. Lobectomy was performed immediately. Postoperatively, the patient fully recovered. After continued antibiotic treatment, follow-up examinations showed negative echocardiographic findings and blood cultures results.